A hierarchical approach for the dynamics of na clusters in contact with an ar substrate - Dinh, P. M.; Douady, J.; Fehrer, F.; Gervais, B.; Giglio, E.; Ipatov, A.; Reinhard, Paul-Gerhard; Suraud, E. (Theoretical and Computational Developments in Modern Density Functional Theory, 2012)
We present a short review on recent theoretical studies of the dynamics of small Na clusters in contact with Ar matrices, in some cases also on NaCl surfaces. We discuss the hierarchical modeling which treats the cluster fully quantum-mechanically and the substrate at a classical level. The dynamical polarizability of the substrate is properly taken into account. We present results on the structural properties, on dynamics in the regime of linear response, and on fully non-linear dynamics induced by strong femtosecond laser pulses. © 2012 by Nova Science Publishers, Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-07-24
Keywords: Hierarchical approach; Interface interaction; Qm/mm; Rare-gas environment; Structure and dynamics of embedded clusters; Time-dependent density functional theory